2004
DOI: 10.1063/1.1790577
|View full text |Cite
|
Sign up to set email alerts
|

The role of the silyl radical in plasma deposition of microcrystalline silicon

Abstract: Expanding thermal plasma chemical-vapor deposition has been used to deposit microcrystalline silicon films. We studied the behavior of the refractive index, crystalline fraction, and growth rate as a function of the silane (SiH4) flow close to the transition from amorphous to microcrystalline silicon. It was found that the refractive index, a measure for film density, increases when the average sticking probability of the depositing radicals decreases. Furthermore, we studied the influence of the position at w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…Finally, the 4-mm arc data do not show a clear dependence on the injection-ring position. This last observation seems to be in contrast with our model published before [5]. In that model we argued that by moving the injection ring towards the substrate, the interaction time between the species emanating from the arc (mainly atomic H) and the SiH 4 was reduced.…”
Section: Resultscontrasting
confidence: 79%
See 3 more Smart Citations
“…Finally, the 4-mm arc data do not show a clear dependence on the injection-ring position. This last observation seems to be in contrast with our model published before [5]. In that model we argued that by moving the injection ring towards the substrate, the interaction time between the species emanating from the arc (mainly atomic H) and the SiH 4 was reduced.…”
Section: Resultscontrasting
confidence: 79%
“…In another article we gave an explanation for the different slopes in Fig. 1(c) [5]. It could be argued that this is due to the varying mass density of the films, as suggested by the varying refractive indices in Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The plasma diagnostics reveals that the density of neutrals in the RF plasma is much higher than the ions. Among the various radicals present in plasma, the SiH 3 density exceeds over SiH and SiH 2 radicals [34,35]. Drevillon et al [36] studied silane plasma using mass spectroscopy and found that SiH 3 + and SiH 3 were responsible for growth of a-Si:H at lower (b5 mTorr) and higher (N100 mTorr) pressure, respectively.…”
Section: Discussionmentioning
confidence: 98%